Mapping Practical Digital Thinking in Nepal to International Digital Literacy Frameworks - Devkota, Nishchal; Prasai, Sadhana; Giri, Sunita; Singh, Avishek; Zazai, Ilyas Khan (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Nepal is shifting from traditional, intuition-based workflows to digitally driven approaches in governance and healthcare. Digital thinking, encompassing competencies such as data-driven decisions, task automation, mobile-first and user-centered design, cloud collaboration, remote work, predictive analytics, digital security, creativity, adaptability, networked decision-making, and sustainability, provides a framework for this transformation. This narrative review examines the adoption and challenges of these dimensions in Nepal, highlighting their potential to improve public health, administrative efficiency, and citizen engagement. Mapping these practical dimensions to DigComp 2.1 and United Nations Educational, Scientific and Cultural Organization (UNESCO) Digital Literacy Framework offers a structured approach for guiding policy and practice. Addressing gaps in literacy, infrastructure, and cybersecurity can accelerate Nepal’s digital transformation and enhance health outcomes.